(untitled) (Brazilian Journal of Radiation Sciences (BJRS), 2015)
Computed tomography is considered a high radiation dose modality, and therefore establishment of diagnostic reference levels is highly recommended. These levels are expected not to be exceeded for standard procedures, when good practice is applied. Most CT scanners display a dose index, CTDIvol. For pediatric studies, this dose index is measured using a standard phantom and an ionization chamber, and does not represent patient dose, but a reference measurement. The objective of this study was to investigate the CTDIvol dose descriptor in head CT scans of a sample of pediatric patients, comparing them with the DRL presented in the literature. Data of head CT without contrast of 40 pediatric patients were retrospectively collected. The acquisition parameters of each examination were extracted from DICOM header and analyzed to assess the protocols typically used by technicians. The mean values of CTDIvol of each group were compared with the DRL values from literature. The measurement of accuracy indicated a difference of 11,6% with the CTDIvol registered by the scan, which can be explained by six different protocols used by technicians for the same exam. The variation is specially critic for the youngers than 1 year. Some children were submitted to a protocol with 50% higher dose than others. This group has 4% higher mean CTDIvol than DRL in literature, while other groups have lower values. The results show the role of medical physicist, optimizing clinical protocols to guarantee the maximum image quality with minimum dose.